Preventive Aspects of Vitamin D and Health; an Overview - S.A. Faruqui; Raghvendra Choubey (International Journal of Medical Research and Review, 2014)
Bioactive vitamin D or calcitriol is a steroid hormone that has long been known for its role in regulating body levels of calcium and phosphorus, and in mineralization of bone. Research also suggests that vitamin D is important for muscle strength and performance, stimulates the immune system, helps to treat infection and protects against autoimmune diseases and more than a dozen type of cancer, including prostate, breast and colon cancer. The relevance of the frequently low vitamin D status is not completely clear. There is growing evidence for the contribution of a circulating 25(OH)D level below 50 nmol/l to the development of various chronic diseases.